ПРОНИЦАЕМОСТЬ КИШЕЧНОЙ СТЕНКИ У ДЕТЕЙ С НОВОЙ КОРОНАВИРУСНОЙ ИНФЕКЦИЕЙ - Полунина, Анна Владимировна; Новикова, Валерия Павловна; Блинов, Александр Евгеньевич; Варламова, Ольга Николаевна; Белова, Анна Александровна; Балашов, Алексей Львович; Баннова, Светлана Леонидовна; Воронцов, Павел Владимирович; Белевич, Светлана Вячеславовна (FORCIPE, 2022)